Fish - Evans, Mark, 1962-; Caras, Roger A. (New York : Dorling Kindersley, 1993)
Describes how to set up and maintain an aquarium and how to care for fish as household pets. Includes information on choosing your new fish, preparing cold-water and warm-water tanks, feeding your fish, and keeping your fish happy and healthy.
Includes index.
Wilson's Children.
4.9.
4.9
3-6
Keywords: Aquarium fishes -- Juvenile literature; Aquariums -- Juvenile literature; Aquarium fishes; Aquariums; Aquariums; Fishes